2022
DOI: 10.3390/vaccines10040537
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Vaccine Hesitancy among Community Hospitals’ Healthcare Workers in Singapore

Abstract: COVID-19 has culminated in widespread infections and increased deaths over the last 3 years. In addition, it has also resulted in collateral economic and geopolitical tensions. Vaccination remains one of the cornerstones in the fight against COVID-19. Vaccine hesitancy must be critically evaluated in individual countries to promote vaccine uptake. We describe a survey conducted in three Singapore community hospitals looking at healthcare workers’ vaccine hesitancy and the barriers for its uptake. The online an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
4
18
0
1
Order By: Relevance
“…This finding is very crucial as HCWs play a key role in guiding local communities’ attitudes toward vaccination [ 108 ]. In addition, HCWs’ vaccination beliefs and attitudes are critical for primary prevention strategies [ 109 , 110 ]. However, this estimate should be interpreted in light of the relatively low number of studies and HCW participants compared with the general public.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is very crucial as HCWs play a key role in guiding local communities’ attitudes toward vaccination [ 108 ]. In addition, HCWs’ vaccination beliefs and attitudes are critical for primary prevention strategies [ 109 , 110 ]. However, this estimate should be interpreted in light of the relatively low number of studies and HCW participants compared with the general public.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that COVID-19 vaccines could decrease the severity of coronavirus infection, serious side effects, and death [ 1 , 2 , 3 ]. Despite the hard scientific evidence, many people, especially young adults, remain unvaccinated [ 4 , 5 , 6 , 7 , 8 , 9 ]. Vaccination prevalence seems to differ depending on geographic region or country [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low rate of influenza vaccination among HCPs in Lahore, Pakistan, is likely related to the unfamiliarity of vaccine availability, cost of the vaccine, and some concerns/beliefs about influenza vaccination. Various socio-demographic factors, e.g., age, gender, marital status, and education level, have been found to be associated with vaccine hesitancy during the pandemics of HINIpdm09 and COVID-19 [ 28 , 29 , 30 ]. In our study, vaccine hesitancy was frequent in young people (age 21–30) compared to older age (>30 years).…”
Section: Discussionmentioning
confidence: 99%